Identification of variants responsible for primary immunodeficiency disease in South African patients using whole genome sequencing - Swart, Robin Grant (Stellenbosch : Stellenbosch University, 2021)
ENGLISH ABSTRACT: Primary immunodeficiencies (PID), also referred to as Inborn Errors of Immunity (IEI), are a group of genetic disorders, caused by inherited or de novo mutations in genes encoding components of the immune system, which results in impaired immune function. These disorders range in severity from almost invariably fatal to asymptomatic. However, these critically underreported and misdiagnosed group of disorders typically go undiagnosed for several years, with the majority having developed a further permanent impairment in the interim. Whilst previously believed to be rare genetic disorders, the most recent International Union of Immunological Societies (IUIS) estimates of PID prevalence are 1:1000-1:5000. Developing countries such as South Africa are expected to have the same prevalence of PID as developed countries and South Africa suffers from many of the typical confounding factors surrounding the underreporting and misdiagnosis of PID, leading to it being vastly underrepresented. In addition to this South Africa’s high infectious disease burden, particularly human immunodeficiency virus (HIV) and tuberculosis (TB) make PID a significant concern. Over the years the use of next generation sequencing (NGS) panels specific for PID have been used for the rapid identification of PID, however, the use of more comprehensive but time-consuming NGS methods such as whole exome sequencing (WES) and whole genome sequencing (WGS) have increasingly come into focus. These NGS tools provide a more comprehensive analysis of patients’ exomes and genomes respectively, for the identification of potential PID causing variants, irrespective of whether they are covered by current panels and known research or whether they are novel. Of the two NGS technologies WGS is more comprehensive and accurate than WES, but also more time consuming to process and currently more expensive, yet it is becoming increasingly more affordable. This study investigated individuals suffering from various PIDs, with the aim of identifying the potential molecular defects responsible by means of NGS, as well as comparing two NGS platforms. The latter aim entailed the comparison of the Ion Proton (WES) platform to the MGI-Seq2000 (WGS) platform and to determine if WGS may be more viable than WES as a first line broad genetic test for PID patients, without a molecular diagnosis, in a South African context. Thus, these patients underwent WES on the Ion Proton platform for variant analysis and interpretation. Ultimately no Sanger confirmed WES candidate variants were identified. This in conjunction with the high number of false positives observed from the sequence data generated on the Ion Proton platform, warranted further follow up and comparative analysis on these patients’ using WGS on the MGI-Seq2000. However, only two patients’ (PID_016 and PID_058) DNA samples were ultimately of sufficient quality and quantity to undergo WGS and thus WGS derived variant filtration and analysis. Unfortunately, no Sanger confirmed candidate variants were identified based on WGS either. Therefore, comparative analysis of WES and WGS was not particularly viable and thus was unable to establish a clear indicator of which performed better in this study. However, during this study seven false positive variants in seven genes, RAG1, IFIH1, IL34, DTX4, IL12B, TAPBP and DOCK2, were identified in the Ion Proton sequencing data, and were Sanger confirmed as false positive. These false positives were not detected in the corresponding patients WGS data. In summary, this study presents information which may aid future research of rare genetic disorders, by assisting in the consideration of different NGS platforms, as well as the strategies that should be employed for candidate variant selection.